Iκκ Mediates NF-κB Activation in Human Immunodeficiency Virus-Infected Cells - Asin, Susana (American Society for Microbiology, 1999)
Human monocytes and macrophages are persistent reservoirs of human immunodeficiency virus (HIV) type-1. Persistent HIV infection of these cells results in increased levels of NF-κB in the nucleus secondary to increased IκBα, IκBβ, and IκBɛ degradation, a mechanism postulated to regulate viral persistence. To characterize the molecular mechanisms regulating HIV-mediated degradation of IκB, we have sought to identify the regulatory domains of IκBα targeted by HIV infection. Using monocytic cells stably expressing different transdominant molecules of IκBα, we determined that persistent HIV infection of these cells targets the NH(2) but not the COOH terminus of IκBα. Further analysis demonstrated that phosphorylation at S(32) and S(36) is necessary for HIV-dependent IκBα degradation and NF-κB activation. Of the putative N-terminal IκBα kinases, we demonstrated that the Iκκ complex, but not p90(rsk), is activated by HIV infection and mediates HIV-dependent NF-κB activation. Analysis of viral replication in cells that constitutively express IκBα negative transdominant molecules demonstrated a lack of correlation between virus-induced NF-κB (p65/p50) nuclear translocation and degree of viral persistence in human monocytes.